Dynamic voltage restorer (DVR) in a complex voltage disturbance compensation - Mansor, Muhammad Alif; Othman, Muhammad Murtadha; Musirin, Ismail; Noor, Siti Zaliha Mohammad (International Journal of Power Electronics and Drive Systems (IJPEDS), 2019)
Nowadays, a distribution network is operating in a stressful manner because of a complex voltage disturbance stirred by its nonlinear, intensified, sensitive and complex loading condition with vast proliferation of electronic equipment required for the integration of renewable energy. A distribution network that mostly inflicted by the complex voltage disturbance can be referred to as the merge of stationary voltage disturbances with a short duration voltage disturbance under a nonlinear loading condition. Therefore, the dynamic voltage restorer (DVR) integrating with the battery bank will have enough energy storage to overcome long and deep complex voltage disturbance that occurs in a distribution network installed with the photovoltaic (PV) system. The results are obtained with satisfactorily findings in compensating the complex voltage disturbance using DVR.